Differences in catheter-related complications to insertion site selection for long peripheral intravenous catheters in antimicrobial therapy: a randomized controlled trial - Linfang Zhao; Xianghong Jin; Xiangyun Li; Chang Liu; Jie Wang; Xiuzhu Cao; Xufen Zeng; Yiyu Zhuang (BMC Nursing)
Abstract Background The long peripheral intravenous catheter (long PIVC), a type of PIVC, has an indwelling time of 5–14 days and is one of the options for antibacterial therapy. However, there is no consensus regarding the impact of insertion site selection on the complications associated with long PIVCs. Methods This randomized controlled trial included 90 participants randomly assigned to either the control or experimental group, with 45 patients in each group. In the control group, long PIVCs were placed in the forearm, while in the experimental group, they were inserted in the upper arm. The primary outcome was catheter-related complications, while secondary outcomes included the first-attempt insertion success rate, total procedure time, and indwelling catheter duration. Results The incidence of catheter-related complication rates was significantly lower in the experimental group (25.0%) compared to the control group (66.7%) (χ2 = 14.528, P < 0.001). The median indwelling catheter duration (interquartile range [IQR]) in the experimental and control groups were 187 [129, 286] hours and 122 [96, 188] hours, respectively, and the difference was statistically significant (Z = 3.016, P < 0.001). The first-attempt insertion success rates were comparable between the experimental group (97.7%) and the control group (97.4%). Similarly, the median total procedure times (IQR) in the experimental and control groups were 5.55 [4.93, 7.48] minutes and 6.17 [5.00, 7.33] minutes, showed no statistically significant difference (Z = 0.511, P > 0.05). Conclusions Selecting the upper arm as the insertion site for long PIVCs reduced the incidence of thrombophlebitis and extended indwelling catheter duration during antimicrobial therapy. Trial registration ClinicalTrials.gov identifier: NCT06455228 (Initial Release: 05/30/2024).